2022
DOI: 10.1128/spectrum.02255-22
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Low-Biomass Sample Collection and Quantitative PCR-Based Titration Impact 16S rRNA Microbiome Resolution

Abstract: The interaction between the fish gill and surrounding bacteria-rich water provides an intriguing model for examining the interaction between the fish, free-floating bacteria, and the bacterial microbiome on the gill surface. Samples that are inherently low in bacteria, or that have components that inhibit the ability to produce libraries that identify the components of microbial communities, present significant challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…To date, very few comparative studies focused on mucosalassociated microbiota when using different sampling methods have been performed in fish mucosal tissues, such as gills (57)(58)(59), skin (60), and gut (61), which have obtained some controversial results. In the gastrointestinal tract, there has been shown evidence of a divergent composition between the bacteria weakly adhering to the intestinal mucosa collected by washing and those obtained when scraping the mucosa in European whitefish (Coregonus lavaretus) (61).…”
Section: Resultsmentioning
confidence: 99%
“…To date, very few comparative studies focused on mucosalassociated microbiota when using different sampling methods have been performed in fish mucosal tissues, such as gills (57)(58)(59), skin (60), and gut (61), which have obtained some controversial results. In the gastrointestinal tract, there has been shown evidence of a divergent composition between the bacteria weakly adhering to the intestinal mucosa collected by washing and those obtained when scraping the mucosa in European whitefish (Coregonus lavaretus) (61).…”
Section: Resultsmentioning
confidence: 99%
“…Further refinement of non‐lethal methods and validation studies of these methods would also be beneficial. There has been some movement in the past few years toward fish‐specific microbiome method evaluations (see Clinton et al, 2021; Clokie et al, 2022; Hildonen et al, 2019; Nyholm et al, 2022). Ideally, the research community will converge on a set of best practices that provide repeatable and reproducible results for different fish body compartments for microbiome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, fish gut samples have very different chemical and enzymatic profiles, which may result in differing degrees of PCR inhibition (Hildonen et al, 2019). Fish gill samples also prove to be rich in PCR inhibitors; however, gill biopsies are likely more problematic than gill swabs due to being a blood‐rich tissue (Clokie et al, 2022). Inhibitors can also be introduced during sample preservation and storage.…”
Section: Challenges With Non‐lethal Microbiome Samplingmentioning
confidence: 99%
“…In total, we sequenced 385 metagenomic and 365 metatranscriptomic swabs comprising ten body sites representing the oral, nasal, and skin microbiomes ( To account for variation due to database and algorithmic bias, we used a diverse set of shortread alignment and de novo assembly approaches to estimate the microbial community taxonomic and functional composition of our dataset (Supplementary Figure 1, Supplementary Tables 2-6, Methods). We observed that many of the swabs collected, especially those from the skin sites, comprised low biomass microbial communities; there are many documented challenges in analyzing these data 30,31 . To filter environmental contamination and the kitome 32 influencing our findings, we collected and sequenced negative controls of both (1) the water that sterile swabs were dipped in prior to use as well as (2) the ambient air around the sites of sample collection and processing for sequencing.…”
Section: Quantifying the Metagenomic Architecture Of Short-term Space...mentioning
confidence: 99%